The EBMT/EMCL consensus project on the role of autologous and allogeneic stem cell transplantation in mantle cell lymphoma - Robinson, Stephen; Dreger, Peter; Caballero, D.; Corradini, P.; Geisler, C.; Ghielmini, M.; Le Gouill, S.; Kimby, E.; Rule, S.; Vitolo, U.; Dreyling, M.; Hermine, O. (Leukemia, 2015)
The role of both autologous (autoSCT) and allogeneic stem cell transplantation (alloSCT) in the management of mantle cell lymphoma (MCL) remains to be clarified. We conducted a consensus project using the RAND-modified Delphi consensus procedure to provide guidance on how SCT should be used in MCL. With regard to autoSCT, there was consensus in support of: autoSCT is the standard first-line consolidation therapy; induction therapy should include high-dose cytarabine and Rituximab; complete or partial remission should be achieved before autoSCT; Rituximab maintenance following autoSCT is not indicated; and omission of autoSCT in ‘low-risk’ patients is not indicated. No consensus could be reached regarding: autoSCT in the treatment of relapsed disease following non-transplant therapy; the value of positron emission tomography scanning and minimal residual disease (MRD) monitoring; in vivo purging with Rituximab; total body irradiation conditioning for autoSCT; and preemptive Rituximab after autoSCT. For alloSCT, consensus was reached in support of: alloSCT should be considered for patients relapsing after autoSCT; reduced intensity conditioning regimens should be used; allogeneic immunotherapy should be used for MRD eradication after alloSCT; and there is a lack of prognostic criteria to guide the use of alloSCT as first-line consolidation. No consensus was reached regarding the role of alloSCT for relapsed disease following non-transplant therapy.
Advance online publication: 29 August 2014
Gesehen am 02.07.2020